2012
DOI: 10.1111/j.1747-4949.2012.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Resistance in Chinese Stroke Patients Increased the Rate of Recurrent Stroke and other Vascular Events

Abstract: Aspirin resistance is common in Chinese patient taking antiplatelet medications. Diabetes and high LDL may induce platelet activation and thrombosis and increase the occurrence of aspirin resistance. Patients who are detected to be aspirin resistant are at a greater risk of clinically important vascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 21 publications
5
57
0
Order By: Relevance
“…Platelet aggregation activity was measured using light transmittance aggregometry before clopidogrel treatment and within 7–10 days after clopidogrel treatment according to a previous study 21) . In brief, 5 mL of fasting venous blood was collected in 660 µL of 3.8% sodium citrate and centrifuged at 200 × g for 10 min to obtain platelet-rich plasma (PRP).…”
Section: Methodsmentioning
confidence: 99%
“…Platelet aggregation activity was measured using light transmittance aggregometry before clopidogrel treatment and within 7–10 days after clopidogrel treatment according to a previous study 21) . In brief, 5 mL of fasting venous blood was collected in 660 µL of 3.8% sodium citrate and centrifuged at 200 × g for 10 min to obtain platelet-rich plasma (PRP).…”
Section: Methodsmentioning
confidence: 99%
“…Platelet aggregation was measured by light transmittance aggregometry (LTA), as described previously [2, 5, 18]. A mean aggregation of ≥70% with 10 μM ADP and a mean aggregation of ≥20% with 0.5 mM AA after aspirin intake for 7 to 10 days were defined as AR.…”
Section: Methodsmentioning
confidence: 99%
“…Aspirin is routinely used for the treatment of IS [3], and its use is associated with improved outcomes [2, 4]. However, recent studies have shown that aspirin resistance (AR) can lead to the failure of antiplatelet therapy [5], and is associated with frequent END and ERIS in patients with acute IS [6, 7]. Thus, further identification of risk factors for AR could improve the treatment of patients at risk of IS, enabling clinicians to choose more effective treatments.…”
Section: Introductionmentioning
confidence: 99%
“…None of the studies published to date have been adequately powered to definitively comment on whether ex vivo HTPR status on platelet function testing in CVD patients predicts the risk of recurrent vascular events. Evidence pertaining to the relationship between antiplatelet-HTPR status and functional outcome, stroke severity and mortality on antiplatelet therapy following TIA or stroke is emerging, but available data from small-medium sized studies need to be validated in larger studies [51,64,66,92,93]. Furthermore, with the exception of three studies [45,51,64], duration of clinical follow-up has been relatively short.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study in CVD patients with prospective follow-up assessed ex vivo 'aspirin resistance' in 634 Chinese stroke patients on 200 mg of aspirin daily with optical aggregometry using PRP [51]. Aspirin resistance (AR) was defined as a mean aggregation of !…”
Section: Platelet Aggregometrymentioning
confidence: 99%